Landasan Filosofis Pendidikan Islam dan Implikasinya pada Sistem Pendidikan di Lembaga Pendidikan Madrasah Aliyah Sholihiyyah - Sani, Mutiara; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2025)
Islamic education is grounded in philosophical principles that integrate divine revelation, reason, and local cultural values as the foundational pillars in shaping the educational system within Islamic institutions. This article aims to examine the philosophical foundations of Islamic education, including the concepts of tauhid, revelation, and reason, as well as their implications for institutional structure, curriculum development, and teaching methods. Using a qualitative approach and theoretical review, this study reveals that these philosophical foundations shape a holistic, integrated, and value-driven Islamic education system oriented toward the development of individuals who are faithful, knowledgeable, and morally upright. The practical implications are evident in the development of curricula rooted in Islamic values that are responsive to contemporary dynamics and social needs. An Islamic education system based on these philosophical principles enables the creation of learning processes that emphasize not only cognitive development but also spiritual and moral dimensions, making it highly relevant for implementation in modern educational contexts.